Caring for Blind Parents: Cost to the Education and Well-Being of Children in Tamale, Ghana. Issue 1 (2nd January 2016) - Kuyini, Ahmed Bawa; Alhassan, Abdul Razak Kuyini
ABSTRACT: In this study we explored the experiences of the guide children (children who guide adults with visual impairment to beg for a living on the streets) in Tamale, Ghana, to unearth the impact of the guiding role on their educational participation and well-being. Data were gathered from 104 children and 57 adults using a set of questionnaires and interviews. The results showed that adults chose many of the children to take on the guide role and many of the children did not attend school. The implications for the children's well-being are discussed in relation to needs and rights.